A study of the heat flux profile effect on parallel channel density wave oscillation in sodium heated heat exchanger. (April 2019) - Ma, Zaiyong; Zhang, Luteng; Bu, Shanshan; Sun, Wan; Chen, Deqi; Pan, Liangming
Abstract: Because of the heat transfer coefficient varying much from single-phase to two-phase and changes of operation conditions, heat flux profiles in sodium heated heat exchanger(SHHX) should be very different from the usually studied uniform profile for analyzing the parallel channel density wave oscillation (PCDWO). In this paper, the typical heat flux profiles in SHHX were separated and its effects on PCDWO were studied. The results showed that the heat flux profile will have a distinct effect on PCDWO, and the marginal stability boundaries (MSB) will move clearly as heat flux profile changes. However, when the operation condition points of the SHHX were taken into account, in most cases the stability boundaries of different heat flux profiles would follow the movement of operation points, making the heat flux profile effect be a factor enhancing the SHHX stability. Because of the heat flux profile effects, impacts of many parameters on stability like water inlet temperature would be suppressed, and only the water mass flow, sodium mass flow and water pressure could have distinct effects. Further discussion was performed and the two phase region was found to be dominate in determining the heat flux profile effect, and the normalized boiling onset location was believed to be a better parameter than the subcooling number for analyzing the heat flux profile effect. It was found that the normalized boiling onset location at the intersection point of the MSB curves of two different heat flux profiles may not change when inlet resistance coefficient varied and might decrease with increase of outlet resistance coefficient, and that the stability could be strongly enhanced by large two phase normalized heat flux. On the basis, a criterion that can be used to estimate the effect of heat flux profile at different boiling onset locations for a certain heat flux profile, to compare roughly the relative stability of different heat flux profiles under different conditions or to analyze qualitatively the slopes of the MSB curves was proposed. This study will provide a better understanding of the heat flux profile effects on PCDWO. Highlights: Impacts of operation conditions on SHHX stability were studied considering heat flux profile effect. A criterion was proposed to estimate the heat flux profile effect. Analysis was performed to found the mechanism and properties of heat flux profile effect.